Polarographic Behaviour of Dy(III) on Mercury Drop Cathode† - Rathore, O.P.; Lavale, S.C. (Asian Journal of Chemistry, 2010)
The nature and behaviour of reduction of Dy(III) on a mercury drop cathode has been extensively investigated. It was observed that Dy(III) gave a single step well defined reduction wave in KCl in the entire range of pH 2.1 to 3.4. Above this pH value aquo ions have a predominant role. The reduction has been found to be diffusion controlled and variation in wave height and concentration was linear. The effect of pH, supporting electrolyte concentration and Dy(III) concentration have been observed. The polarographic reduction of Dy(III) is abnormal. It produces reversible, quasireversible and irreversible reduction wave under distinct experimental conditions. The log plot analysis of each of the polarograms revealed that Dy(III) produces a reversible three electron wave at pH 2.6 to 0.5 mole dm–3 KCl and 0.01% gelatin E½, id and E¾ – E¼ values are –1.72 V, 3.9 and 19 mV respectively.